A Method for Comparison of Northern Fossil Insect Assemblages - Matthews, John V. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1983)
ABSTRACTThe paleoenvironmental resolving power of late CenozoicColeoptera fossils from arctic and subarctic sites is hindered by the fact that the fossil assemblages often differgreatly in taxonomic diversity and minimum number of individuals represented. In order to compare faunas of different age and from different sites, the fossil insect assemblages must first be normalized. One method of doing this is to group the fossils according to the ecological requirements of the taxa that they represent and then compare assemblages on the basis of the percentage of individual insects in each group. Eight such groups are defined in this paper and then used to compare fossil assemblages from the Yukon Territory, Alaska and eastern Siberia. Such comparisons reveal differences related to local site-of-deposition conditions but they also reflect the character of the regional late Pleistocene beetle fauna. The grouping procedure supports conclusions based on other information, such as taxonomic content, but it masks certain assemblage characteristics that may also be of paleoenvironmental significance. Thus grouping insect fossils as a means of normalizing the dataf or purposes of comparison should not be used in lieu of other analytical approaches.